Cromosomopatías en pacientes con cáncer sometidos a radioterapia con cobalto 60 - Fernández Barrero, Claudia (2022)
Aim: The objective of this study was to describe the before and after cytogenetic aberrations found in current patients of radiotherapy. This can be observed through the technique called “Giemsa in fluorescence”.Methods: A minimum of 200 metaphases were analyzed in the first mitotic division in 9 patients, The patients where observed before and after radiotherapy treatment at the San Juan de Dios Hospital in Costa Rica. In each case, any type of chromosomopathy was counted using the “Giemsa in fluorescence” test as well as Bromodeoxyuridine and acridine orange.Results: The chromosomopathies are observed before and after treatment with radiotherapy. The treatment seems to change the frecuency, increasing the dicentric chromosomes, and centric rings after the treatment. The frequency of chromatid fractures, satellite associations, and morphological alterations were not affected by radiotherapy.